(3GdESaGQ ef Mce GdCSaGQs - (3GHf GdCeTGWj , eMehO Hf CMeO Hf MSf Hf ESeGYjd, eXaQ GdOjf CHh GdKfGA,J (B902 (3g` s ((3eMeO Hf Ydi Hf eMeO GdbdJi GdCRgQi s)
(3ChdgG (B:s
(3GdMeO ddg GdPi CeQ HGdCSaGQ ddJacQ hGdGYJHGQ QCjJ Cf CLeY cJGHkG CQTO ajg Edi Pdc , SGdckG ajg CLed GdeSGdc , aLCA HMeO Gddg MGhjkG dCSQGQ cJH gPG Gdaf s
(3BNQgG (B:s
(3ef cd hGMO LRA , LdfGQ fUa LRA gPG BNQ eG CQOfG Yedg Je GdcJGH s
(3Vef eLehY s
(3GfXQg eY OaY GdSehe Qbe (B" 467"s
(3bQf GdfSN (B:s
(3GdbQf GdYGTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B163 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B12 - (3U (B145s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA WH (B- (3bSe GdcJGH GdKfi (B- (3U (B22 s
Keywords: (3GdWHs